Unusual case of hemidiaphragmatic paralysis secondary to cervical herpes zoster. (23rd January 2018) - Saleem, Muhammad Adnan; Mustafa, Zeeshan; Qayyum, Noman; Ganaie, Muhammad Badar
Abstract : Hemidiaphragmatic paralysis is usually caused by surgery, malignancy or trauma and rarely by viral infections. Herpes zoster (shingles) results in varied neurological complications, but peripheral motor involvement or diaphragmatic paralysis is rare. We report the case of an 87-year-old male who presented with worsening breathlessness soon after an episode of shingles, affecting his right neck and upper chest. He had no alarm symptoms, history of trauma or malignancy. Skin lesions resolved after a few weeks, but his breathing did not improve. Chest X-ray revealed a new finding of elevated right hemidiaphragm; diaphragmatic ultrasound confirmed paradoxical cranial movement of right hemidiaphragm on sniff testing. CT scan showed no lung mass and complete collapse of right lower lobe due to elevated right hemidiaphragm. Patient has required no treatment and is under regular follow-up with the ventilation clinic.